Nanofibrous wound dressing material by electrospinning method - İNAN, AHMET TALAT; OKTAR, FAİK NÜZHET; EKREN, NAZMİ; GÜNDÜZ, OĞUZHAN; KILIÇ, OSMAN (TAYLOR & FRANCIS AS, 2019)
Wound dressings are very useful materials for accelerating the wound healing process. In this study, nanofibrous wound dressings were produced from blending solution of Poly-lactic acid(PLA)/Chitosan(C)/Starch(S)/Zinc oxide(Z) by electrospinning method. Morphology, chemical interaction, mechanical, water uptake and weight loss tests were performed on each samples. Moreover, the biocompatibility of primary dermal fibroblast (ATCC, PCS-201-012) on prepared wound dressings was investigated with MTT assays in vitro, and the samples were found suitable for cell viability and proliferation. These results suggest that produced nanofibrous wound dressings can be promising candidate for wound dressing applications. [GRAPHICS] .
Keywords: Electrospinning; polymer; wound dressing; zinc oxide; ZINC-OXIDE; ANTIMICROBIAL ACTIVITY; CHITOSAN; BIOMATERIALS; DEACETYLATION; FABRICATION; EXTRACT; SKIN